Ubiquitin‐specific protease USP34 controls osteogenic differentiation and bone formation by regulating BMP2 signaling - Guo, Yu‐chen; Wang, Meng‐yuan; Zhang, Shi‐wen; Wu, Yun‐shu; Zhou, Chen‐chen; Zheng, Ri‐xin; Shao, Bin; Wang, Yuan; Xie, Liang; Liu, Wei‐qing; Sun, Ning‐yuan; Jing, Jun‐jun; et al. (The EMBO journal, 2018)
The osteogenic differentiation of mesenchymal stem cells (MSCs) is governed by multiple mechanisms. Growing evidence indicates that ubiquitin‐dependent protein degradation is critical for the differentiation of MSCs and bone formation; however, the function of ubiquitin‐specific proteases, the largest subfamily of deubiquitylases, remains unclear. Here, we identify USP34 as a previously unknown regulator of osteogenesis. The expression of USP34 in human MSCs increases after osteogenic induction while depletion of USP34 inhibits osteogenic differentiation. Conditional knockout of Usp34 from MSCs or pre‐osteoblasts leads to low bone mass in mice. Deletion of Usp34 also blunts BMP2‐induced responses and impairs bone regeneration. Mechanically, we demonstrate that USP34 stabilizes both Smad1 and RUNX2 and that depletion of Smurf1 restores the osteogenic potential of Usp34‐deficient MSCs in vitro . Taken together, our data indicate that USP34 is required for osteogenic differentiation and bone formation. Synopsis Combining in vitro and in vivo approaches, this study identifies ubiquitin‐specific protease USP34 as a new regulator of osteogenesis. USP34 activates BMP2 signaling by deubiquitinating and stabilizing Smad1 and RUNX2, thereby promoting osteogenic differentiation. Depletion of USP34 impairs osteogenic differentiation in vivo and in vitro . Usp34‐depleted mice have low bone mass. USP34 is required to activate BMP2 signaling during bone formation. USP34 stabilizes Smad1 and RUNX2 by deubiquitination. USP34 counteracts ubiquitin ligase Smurf1, which targets Smad1 and RUNX2. Graphical Abstract Combining in vitro and in vivo approaches, this study identifies USP34 as a new regulator of osteogenesis via targeted stabilization of Smad1 and RUNX2, illustrating a role for protein deubiquitination in bone formation.